Decrease of Aluminum and Helminth eggs present in dehydrated sludge from the wastewater treatment plant through electrochemical processes - Duque Sarango, Paola Jackeline (2018)
The present article studied the electrochemical treatment in waste sludge from a Wastewater Treatment Plant (WWTP) through the operation of a pilot plant, consisting of 3 tanks or electrolytic cells, whose electrodes were copper plates and graphite at different distances; 7.5, 15 and 12 cm in the tanks A, B and C respectively, in them approximately 6800 cm3 of hydrated sludge were placed with 12% sodium chloride. When the plates were in contact with the mud, they were exposed to a direct current of 12 volts, 4 samples were taken in each of the 3 tanks, which obey contact times of 1 to 4 hours. In the laboratory phase were measured: pH, conductivity, temperature, humidity, sodium hypochlorite and analyzed the reduction of the concentration of aluminum and helminth eggs after treatments. It was found that the percentage of residual aluminum is the same for any of the cells, whether it is A, B or C; however, cell B has a smaller dispersion according to the Levene statistic. A 100% removal of helminth eggs was also achieved in all trials.